Management of congenital ichthyoses: European guidelines of care, part one. (3rd December 2018) - Mazereeuw‐Hautier, J.; Vahlquist, A.; Traupe, H.; Bygum, A.; Amaro, C.; Aldwin, M.; Audouze, A.; Bodemer, C.; Bourrat, E.; Diociaiuti, A.; Dolenc‐Voljc, M.; Dreyfus, I.; et al.
Summary: These guidelines for the management of congenital ichthyoses have been developed by a multidisciplinary group of European experts following a systematic review of the current literature, an expert conference held in Toulouse in 2016 and a consensus on the discussions. They summarize evidence and expert‐based recommendations and are intended to help clinicians with the management of these rare and often complex diseases. These guidelines comprise two sections. This is part one, covering topical therapies, systemic therapies, psychosocial management, communicating the diagnosis and genetic counselling. Abstract : Linked Comment:  Levy. Br J Dermatol 2019;180 :253 .